Reforming child welfare - Golden, Olivia (Urban Institute Press)
What does it take to reform child welfare? -- Building the airplane while flying it: the District of Columbia -- Children, families, and the child welfare system: Alabama and Utah in the national context -- What we know: how research can contribute to reform -- The broad brush: vision, strategy, and action -- Information, learning, and performance management as keys to the turnaround -- Accountability and the politics of performance improvement -- Leadership -- Taking reform to the front lines -- Recommendations